The Prospects of Ukraine's Integration into Global Value Chains Within the Framework of European Integration - Sevastyanov , Rodion (Journal of Public Governance, 2021)
Objectives: The purpose of the article is to analyze the current current indicator of export-import activity of Ukraine's economy in the context of interaction with European countries.Research Design & Methods: The research methods used in the study are as follows: analysis and study of literature, scientific description, Internet research, observation, statistical and structural , table presentation of data.Findings: The results of the reserach prove that the economical interaction between Ukrainе an EU has economic potential for growth. Statistical trends of growth of indicators of export-import activity in the context of global value chains (GVC) are revealed. The tendency of growth of intensity of economic relations between Ukraine and the EU countries is established. Examples of integration of Ukrainian enterprises into global value chains are given. Statistical analysis showed that export products (mainly agricultural and industrial products) from Ukraine generated 42.1% of total international sales in Eastern Europe in 2020. It was also investigated that more than 70% of Ukrainian IT exports are software development services that are outsourced to third parties.Implications/Recommendations: Recommendations for Ukraine's integration into global business services can include developing services in context of GVC, developing international cooperation between enterprises on global business platforms. The basis for successful integration into GVC must be the development of innovative ecosystems of industrial high technologies. It is important to develop innovative industrial high-tech ecosystems for successful integration into GVC.Contribution/Value Added: The author tries to formulate modern directions of development for further integration of the Ukrainian economy into global value chains in the context of cooperation with EU countries.Article classification: research articleJEL classification: F620, H4, O520